Effect of indium doping on motions of ⟨a⟩-prismatic edge dislocations in wurtzite gallium nitride. (23rd May 2019) - Chen, Cheng; Meng, Fanchao; Ou, Pengfei; Lan, Guoqiang; Li, Bing; Chen, Huicong; Qiu, Qiwen; Song, Jun
Abstract: The influences of indium doping on dynamics of ⟨ a ⟩-prismatic edge dislocation along shuffle plane in wurtzite GaN have been investigated employing classical molecular dynamics (MD) simulations. The dependence of dislocation motion mode and dislocation velocity on indium doping concentration, temperature, and applied shear stress was clarified. Moreover, the simulation results were further analyzed using elastic theory of dislocation and thermal activation theory of dislocation motion, showing excellent agreement with the simulation. Our findings help gain deep insights into modifying dynamic behaviors of TDs through the alloying doping and offer generic tools to the study of other wurtzite materials of promising application prospects, such as AlGaN and ZnO.